STUDENTS’ CYNICAL ATTITUDE TOWARDS STUDYING AND ITS RELATIONSHIP WITH CAREER COMMITMENT AND ACADEMIC BURNOUT - Pociūtė, Birutė; Pečiūra, Žigimantas (Acta Paedagogica Vilnensia, 2014)
Many university and college students are not fully decided about their career choice and often don’t have a strong commitment to the profession they are studying. However, while in study process, students may conflict with some negative aspects. For instance, students are often disappointed about their studies, dissatisfied expectations are one the presumptions which lead to academic cynicism. The aim of this investigation was to reveal the relationship between students’ career commitment, academic burnout, and cynical attitude towards studies. In the present research, 295 bachelor students of the III and IV courses took part. The participants filled in a questionnaire which consisted of an academic cynicism scale (by Dean, Brandes, Dharwadkar, 1998), a career commitment scale (by Meyer, Allen, Smith, 1993), and an academic burnout scale (by Demerouti et al., 2001). The results have shown that career commitment is negatively associated with academic burnout and academic cynicism; academic burnout and academic cynicism correlate positively. According to multiple regression results, academic burnout is a predictor of student career commitment and cynical attitudes towards studies. Meanwhile, academic burnout can be predicted either by the level of career commitment or academic cynicism. Students committed to their career have been found to be more engaged in and more satisfied with their studies and to have better marks. According to the results of the research, students’ career continuance can be predicted by the level of academic cynicism and career commitment.